Public Relations and Journalism - Pitonakova, Slavka (Communications - Scientific letters of the University of Zilina, 2012)
The paper offers the findings of possible interconnection between journalism and public relations. It was created as a reaction to the need to explore the level of influence (and impact) of public relations worker on journalism. This need was accompanied by the attempt to look into the issue both from the aspects of journalist and public relations worker. We focused on the exploration of media environment (in relation to media market) with respect to possibilities of being influenced by marketing, specifically by the area of public relations.